2019
DOI: 10.1113/jp276943
|View full text |Cite
|
Sign up to set email alerts
|

Human circadian phase–response curves for exercise

Abstract: Key points Exercise elicits circadian phase‐shifting effects, but additional information is needed. The phase–response curve describing the magnitude and direction of circadian rhythm phase shifts, depending on the time of the zeigeber (time cue) stimulus, is the most fundamental chronobiological tool for alleviating circadian misalignment and related morbidity. Fifty‐one older and 48 young adults followed a circadian rhythms measurement protocol for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
147
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(157 citation statements)
references
References 68 publications
(103 reference statements)
7
147
2
1
Order By: Relevance
“…We chose morning and evening exercise for 2 reasons. First, morning exercise has been shown, in some studies, to cause significant phase advances, which could alleviate circadian misalignment in late chronotypes and others whose internal rhythms are delayed relative to the environment (21,33,34). Second, morning and evening are the most common times when people exercise on weekdays, so exercise at these times could be implemented as feasible behavioral interventions for circadian disruption in free-living individuals (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose morning and evening exercise for 2 reasons. First, morning exercise has been shown, in some studies, to cause significant phase advances, which could alleviate circadian misalignment in late chronotypes and others whose internal rhythms are delayed relative to the environment (21,33,34). Second, morning and evening are the most common times when people exercise on weekdays, so exercise at these times could be implemented as feasible behavioral interventions for circadian disruption in free-living individuals (46).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in mice showed that exercise performance, gene transcription, and energy utilization depend on the time of day of exercise (31,32). Clinical studies have conflicting results, but some have shown that morning or early afternoon exercise phase advances, while evening exercise phase delays the internal circadian rhythm (21,(33)(34)(35)(36). However, most of these prior studies were performed in controlled lab conditions, and many studies included physically active adults such that the results may have been confounded by recent nonlaboratory exercise regimens.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…Based on this research, it is expected that the evening exercise has beneficial effects in non-dipping hypertensive men. However, in a recent human study, exercise at the evening and nighttime (from 1900 to 2200 h) delays the phase of melatonin metabolites (14), thus it is possible that evening exercise progress the circadian disturbance of blood pressure via a phase-delay of circadian rhythm. Further studies are required to evaluate the effect of exercise both in terms of hypotensive effect and circadian rhythm is required for the control of circadian blood pressure in hypertensive subjects.…”
Section: Blood Pressure and Blood Circulationmentioning
confidence: 99%
“…Further evidence is expected to lead to a clearer understanding of the molecular mechanisms leading to the interaction between circadian clock and time-of-day effects. Finally, exercise also has the potential for a timekeeper of circadian clock, especially exercise at night-time induces phase-delay in humans (14). Thus, further evidence is needed to discuss the effects of exercise timing in the context of therapeutic effects and its circadian rhythms.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation